The Effect Of Marketing Communication And Service Quality On Product Usage Decisions In Byond By BSI Mobile Banking Through Brand Image As A Mediation Variable: Systematic Literature Review (SLR) With Bibliometrics - Esti Nurwulan; Budi Eko Soetjipto; Madziatul Churiyah (PT. Maju Malaqbi Makkarana, 2026)
The development of digital technology in the banking industry encourages banks to improve the quality of digital services to strengthen the decision to use products by customers. Mobile banking is one of the main innovations used to improve transaction efficiency and customer experience. This study aims to analyze the influence of marketing communication and service quality on product usage decisions in BYOND by BSI mobile banking with brand image as a mediating variable. The method used is Systematic Literature Review (SLR) combined with bibliometric analysis to identify research trends, relationships between variables, and the development of related studies in the scientific literature. The article selection process is carried out through several stages, namely identification, screening, eligibility, and inclusion based on the PRISMA protocol. The data source is obtained from a database of reputable international journals published in recent years and is relevant to the topics of digital marketing, service quality, brand image, and decisions to use digital banking services. The results of the study show that effective marketing communication and good service quality have an important role in forming a positive brand image, which can ultimately improve the decision to use mobile banking products by customers. Bibliometric analysis also shows an increase in research trends related to digital banking, customer experience, and brand perception in recent years. These findings provide strategic implications for banks in designing marketing communications and improving service quality to strengthen brand image and drive the adoption of mobile banking services.